2014
DOI: 10.1155/2014/151952
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacteriophages Infecting Nocardioforms in Wastewater Treatment Plant

Abstract: Activated sludge plants (ASP) are associated with the stable foaming problem worldwide. Apart from the physical and chemical treatment methods, biological treatment method has been least explored and may prove to be a novel and ecofriendly approach to tackle the problem of stable foam formation. In ASP Nocardia species are commonly found and are one of the major causes for forming sticky and stable foam. This study describes the isolation and characterization of three Nocardia bacteriophages NOC1, NOC2, and NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Sewage also provides habitat to a number of human pathogens including human gut microbes, such as Escherichia, Citrobacter, Klebsiella and Enterobacter and phages against them 26 . Therefore, these sources are good starting materials for isolating bacteriophages against epidemiologically important bacterial pathogens and previous studies have isolated phages from these sources 27,28 . In this work, through a systematic approach, we examined the diversity of cultivable microbial populations and isolated phages from wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…Sewage also provides habitat to a number of human pathogens including human gut microbes, such as Escherichia, Citrobacter, Klebsiella and Enterobacter and phages against them 26 . Therefore, these sources are good starting materials for isolating bacteriophages against epidemiologically important bacterial pathogens and previous studies have isolated phages from these sources 27,28 . In this work, through a systematic approach, we examined the diversity of cultivable microbial populations and isolated phages from wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the previous study, we had isolated and tested specific bacteriophages against Nocardioforms -NOC1, NOC2 and NOC3 and showed that they can be used effectively to curb foaming. Their host range was determined and genome sequences studied.…”
Section: Introductionmentioning
confidence: 99%
“…They were demonstrated to be potential inhibitors of nocardioform growth. 1 In the present study, we have discussed the nature of these bacteriophages with respect to temperature and pH. Also, the applicability of this process was studied using lab scale reactors as a preliminary experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Phages isolated from a wastewater treatment plant were shown to have promising potential in controlling biomass bulking caused by the filamentous bacteria Haliscomenobacter hydrossis 32 . Sludge – associated Mycolata hosts for which phages have been identified include Tsukamurella spp., Gordonia , Rhodococcus , Nocardia 22 33 34 35 . Two of these phages - GTE2 and GTE7 - were demonstrated to reduce their host level and prevent stable foam production by their host bacteria in pure laboratory cultures tested in a laboratory foaming apparatus 33 36 .…”
mentioning
confidence: 99%